PENGEMBANGAN WEBSITE PEJABAT PENGELOLA INFORMASI DAN DOKUMENTASI BERBASIS WORDPRESS - Jihan Surfina; Hadiansyah Ma’sum (Jurnal Manajamen Informatika Jayakarta, 2026)
Public information disclosure is a fundamental obligation of government agencies in accordance with Law No. 14 of 2008. As public agencies, obstacles often arise in conventional data management methods that slow down information accessibility for the public. To overcome these problems, a structured Information and Documentation Management Officer (PPID) information system was developed using the WordPress Content Management System (CMS). The system was developed using the Waterfall model, which includes the stages of needs analysis, interface design, feature implementation, functionality testing, and systematic periodic maintenance. The result of this development is the creation of a dynamic and responsive PPID portal, which has proven to facilitate administrators in updating data without requiring in-depth programming skills. The implementation of the CMS-based system has succeeded in increasing the effectiveness of public information services, ensuring agency transparency, and significantly accelerating the distribution of digital documents.